Simultaneous Output-Feedback Stabilization For Continuous Systems - AL-Sunni, Fouad (2020)
A design technique for the stabilization of M linear systems by one constant output-feedback controller is developed. The design equations are functions of the state and the control weighting matrices. An example of the stabilization of an aircraft at different operating points is given.